Use of Antibiotic-impregnated Polymethylmethacrylate (PMMA) Plates for Prevention of Periprosthetic Infection in Breast Reconstruction. Issue 1 (18th January 2023) - Johnstone, Thomas; Lipman, Kelsey; Makarewicz, Nathan; Shah, Jennifer; Turner, Elizabeth; Posternak, Victoria; Chang, Daniel; Thornton, Brian; Nazerali, Rahim
Abstract : Background: Periprosthetic infections remain a major challenge for breast reconstruction. Local antibiotic delivery systems, such as antibiotic beads and spacers, have been widely used within other surgical fields, but their use within plastic surgery remains scarce. In this study, we demonstrate the use of antibiotic-impregnated polymethylmethacrylate (PMMA) plates for infection prophylaxis in tissue expander (TE)-based breast reconstruction. Methods: A retrospective review of patients who underwent immediate breast reconstruction with prepectoral TEs over the span of 5 years performed by two surgeons was completed, revealing a total of 447 patients. Data pertaining to patient demographics, operative details, and postoperative outcomes were recorded. Fifty patients underwent TE reconstruction with the addition of a PMMA plate (Stryker, Kalamazoo, Michigan) impregnated with tobramycin and vancomycin. Antibiotic plates were removed at the time of TE-to-implant exchange. Patient-matching analysis was performed using the 397 patients without PMMA plates to generate a 50-patient nonintervention cohort for statistical analysis. Results: The intervention cohort (n = 50) and 1:1 patient-matched nonintervention cohort (n = 50) demonstrated no statistically significant differences in patient demographics or operative characteristics other than PMMA plate placement. The rate of operative periprosthetic infection was 4% in the intervention group and 14% in the nonintervention group ( P = 0.047). The rate of TE explantation was also reduced in the intervention group (6% versus 18%; P = 0.036). Follow-up averaged 9.1 and 8.9 months for the intervention and nonintervention groups, respectively ( P = 0.255). Conclusion: Local antibiotic delivery using antibiotic-impregnated PMMA plates can be safely and effectively used for infection prevention with TE-based breast reconstruction.